العجز في الموازنة العامة و طرق معالجته في النظام المالي الإسلامي مع المقارنة بالأنظمة الوضعية بحث مستل من أطروحة الدكتوراه في كلية العلوم الإسلامية/ جامعة السليمانية - شريف, باقي كريم; اهلل, عثمان محمود سعيد; علي, خالد حيدر عبد (Sulaimani Journal for Humanities, 2021)
The researcher explained the concept of financial deficit in the state budget in the language and terminology of finance experts and economists in two systems- Isla in two systems- Islamic and positional, than he searched for its causes, negative effects, and methods of solution with it in financial system . After that, he focused on presenting the most important causes of the financial deficit and its solution in the Islam financial system. in addition to highlighting the solution of the financial deficit, and what distinguishes it in this field of methods and the solution means, where it depends on Islamic financial system to address the fiscal deficit in the public budget in three types of methods and means, which are : preventive methods, the used financial methods used, and investment means . And the researcher has concluded that the deficit in the public budget of kinds does not extend its consequences even it is planned if it is not dealt by administrative responsibility, know-how and accurate planning.